THE QUALITY OF STUDENT WORKSHEETS (LKPD) ON WRITING DESCRIPTION TEXT THROUGH FISHBONE DIAGRAM STRATEGY - Rahimi Ulfi; Charlina; Elvrin Septyanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Research on the quality of Student Worksheets (LKPD) using the fishbone diagram strategy aimed to determine the quality of the product in the form of Student Worksheets, which were used as teaching material media to help students develop writing skills. This approach was intended so that students would not experience difficulties when learning descriptive text writing. The LKPD used the fishbone diagram strategy, which resembled a fishbone, to support speaking and writing skills. This research was conducted using a research and development (R&D) method. The data analysis technique applied was quantitative description. The results showed that Student Worksheets for writing descriptive text using the fishbone diagram strategy were feasible to be used as companion teaching materials. Validation results from material experts indicated percentages of 97.6% and 91.7%, while validation from linguists achieved percentages of 88% and 86%. Feasibility tests conducted by field experts (teachers) obtained percentages of 93.68% and 94.73%, and trials with grade VII students of SMP Negeri 1 Kota Dumai reached 84.62%. Keywords: ,